2017
DOI: 10.1103/physrevmaterials.1.011201
|View full text |Cite
|
Sign up to set email alerts
|

Epitaxy and structural properties of (V,Bi,Sb) 2Te3 layers exhibiting the quantum anomalous Hall effect

Abstract: The influence of Sb content, substrate type and cap layers on the quantum anomalous Hall effect observed in V-doped (Bi,Sb)2Te3 magnetic topological insulators is investigated. Thin layers showing excellent quantization are reproducibly deposited by molecular beam epitaxy at growth conditions effecting a compromise between controlled layer properties and high crystalline quality. The Sb content can be reliably determined from the in-plane lattice constant measured by X-ray diffraction, even in thin layers. Thi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 29 publications
4
22
0
Order By: Relevance
“…Our study highlights the difficulties of doping thin films of the (Bi,Sb) 2 (Se,Te) 3 family of compounds, which is characterized by its layered crystal structure. Doping with a single element, such as Cr [10,57] or V [12,16,19,25], results in ferromagnetically ordered films with a sizable T c and decent crystalline properties, i.e., without the occurrence of secondary phases up to rather high doping concentrations. On the other hand, adding very small amounts of another dopant, in our case V added to Cr:Sb 2 Te 3 , seems to force the formation of the direct telluride Cr 2 Te 3 and prevent the substitutional incorporation of the dopants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study highlights the difficulties of doping thin films of the (Bi,Sb) 2 (Se,Te) 3 family of compounds, which is characterized by its layered crystal structure. Doping with a single element, such as Cr [10,57] or V [12,16,19,25], results in ferromagnetically ordered films with a sizable T c and decent crystalline properties, i.e., without the occurrence of secondary phases up to rather high doping concentrations. On the other hand, adding very small amounts of another dopant, in our case V added to Cr:Sb 2 Te 3 , seems to force the formation of the direct telluride Cr 2 Te 3 and prevent the substitutional incorporation of the dopants.…”
Section: Discussionmentioning
confidence: 99%
“…It has previously been demonstrated that MTIs can be realized by magnetically doping three-dimensional TI materials of the (Bi,Sb) 2 (Se,Te) 3 type with transition metals such as Mn [6][7][8] and Fe [9], and more recently Cr and V [10][11][12][13][14]. In both V-and Cr-doped (Bi,Sb) 2 Te 3 epitaxial thin films, the QAH effect has been successfully demonstrated [4,13,15,16] at extremely low temperatures (<100 mK). Doping Sb 2 Te 3 with V has been reported to exhibit a more stable long-range ferromagnetic order than that of Cr-doped films [17], while retain-ing high magnetic transition temperatures [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…[31] The temperature read by the thermocouple during the growth of all of the layers was kept constant at 190 • C. The Bi/Sb ratio was determined by X-ray diffraction (XRD) measurements of the lateral lattice constant a. [31] It was determined to be 0.21/0.79 in a 9 nm thick film with uniform V doping of 1.5 % of all atoms (device D8 exhibiting the quantum anomalous Hall effect, see section 6). Selective magnetic doping was performed by the time controlled opening and closing of the vanadium cell shutter during the MBE growth, and the magnetic doping concentration was controlled by the vanadium cell temperature.…”
Section: Supplementary Materials 1 Sample Fabricationmentioning
confidence: 99%
“…All investigations are performed on samples with a standard Hall bar geometry prepared by optical lithography, and are equipped with an electrostatic gate that allows tuning of the Fermi level in the layers. The topological insulator heterostructures are (Bi,Sb) 2 Te 3 based, with the magnetic layers doped by V. They are grown using molecular beam epitaxy (MBE) on insulating, hydrogen passivated Si (111) substrates, and are covered in-situ with 10 nm of Te to protect the surface from aging [12,31]. The Bi/Sb ratio is 0.79/0.21 for all samples.…”
mentioning
confidence: 99%
“…The devices we used were made of 9 nm thick films of the ferromagnetic topological insulator V0.1(Bi0.21 Sb0.79)1.9Te3, grown by molecular beam epitaxy (MBE) on a hydrogen passivated Si(111) substrate and covered in-situ by a 10 nm thick Te protective cap [24]. The devices were patterned using standard optical lithography.…”
Section: Sample Fabricationmentioning
confidence: 99%